2004
DOI: 10.1002/cne.20084
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connections of the lateral mediodorsal thalamus in cynomolgus monkeys

Abstract: The prefrontal cortex has been defined as that cortical territory that has "essential or sustaining" connections with the mediodorsal (MD) nucleus of the thalamus. However, recent studies in the monkey have documented projections from MD to the more caudal, agranular regions of the frontal cortex, suggesting that the connections of MD may be characterized by a breadth of distribution and diversity of functional roles too great to be useful as a unifying and defining feature for a specific cortical territory. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 63 publications
(108 reference statements)
3
47
1
Order By: Relevance
“…Recently, D 1 Rs have been localized in neurons expressing calbindin or PV, including those in the mediodorsal thalamus that furnish the main projections to the PFC (Rodriguez-Moral and Cavada, 2003), yet it is unclear whether their axons incorporate the receptor. Nonetheless, the latter terminate in layers deep III and IV, with only few nonvaricose fibers present below this zone (Giguere and Goldman-Rakic, 1988;Erickson and Lewis, 2004). Moreover, the midlayer projections express PV and establish type I axospinous synapses , in agreement with the classic descriptions on sensory cortices (DeFelipe and Jones, 1991).…”
Section: Rs In Excitatory Circuitssupporting
confidence: 79%
“…Recently, D 1 Rs have been localized in neurons expressing calbindin or PV, including those in the mediodorsal thalamus that furnish the main projections to the PFC (Rodriguez-Moral and Cavada, 2003), yet it is unclear whether their axons incorporate the receptor. Nonetheless, the latter terminate in layers deep III and IV, with only few nonvaricose fibers present below this zone (Giguere and Goldman-Rakic, 1988;Erickson and Lewis, 2004). Moreover, the midlayer projections express PV and establish type I axospinous synapses , in agreement with the classic descriptions on sensory cortices (DeFelipe and Jones, 1991).…”
Section: Rs In Excitatory Circuitssupporting
confidence: 79%
“…For example, the excitatory inputs from the medial dorsal thalamic nucleus (MD) synapse primarily on dendritic spines 39 and densely arborize in DLPFC layers deep 3 and 4, but do not innervate the deep cortical layers. 40 Interestingly, functional imaging studies have reported altered activation of the MD during working memory tasks in subjects with schizophrenia. 41 In addition, initial post-mortem studies reported a decrement in the number of MD neurons in subjects with schizophrenia, [42][43][44][45] although more recent studies have failed to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…(Haber et al, 1993;Ray and Price, 1993). These connections, however, are bidirectional (Erickson and Lewis, 2004;McFarland and Haber, 2002;Zikopoulos and Barbas, 2007). Moreover, while cortico-thalamic projections of the specific thalamic relay nuclei follow a general rule of reciprocity, the cortical projections to these thalamic nuclei are more extensive than their projections back to cortex (as seen in other thalamocortical systems) (Darian-Smith et al, 1999;McFarland and Haber, 2002;Sherman and Guillery, 1996).…”
Section: Thalamusmentioning
confidence: 99%